Eksperimentasi Metode Think Pair Share Dalam Pembelajaran Bahasa Arab - Rz. Ricky Satria Wiranata (STAI Terpadu Yogyakarta, 2018)
Arabic is a need to be mastered. Students an use Arabi as a medium of ommunication and tool to undesrstand Islamic treasures. In practice, many students are less interested in learning Arabic. This is due to various things, ranging from the aspets ot the media to aspects of methodology that seem exclusive and difficult to maste. Theexperimentation of applying think pair share in learning Arabic is the solutive effort offered by the researcher so that the learning of Arabic language an be understood easily and interesting so that it can improve the learning result.